Abre los ojos una peĺicula de Alejandro Amenábar ; Summit Entertainment y Artisan Entertainment ; una producción de José Luis Cuerda para Sogetel ; Las Produccciones del Escorpión, Les Films Alain Sarde, Lucky Red, con la participación de Sogepaq y la colaboración de Canal+ España ; guión, Alejandro Amenábar y Mateo Gil ; director, Alejandro Amenábar. - Cuerda, José Luis; Cuerda, José Luis; Amenábar, Alejandro, 1972-; Amenábar, Alejandro, 1972-; Bovaira, Fernando; Gil, Mateo, 1972-; Cruz, Penélope; Noriega, Eduardo, 1973-; Lera, Chete; Martínez, Fele; Nimri, Najwa, 1972- (Twentieth Century Fox [Distributor] : Sogepaq, 2000)
A womanizing, handsome young man falls in love with his friend's girlfriend, Sofia. In suicidal rage, his current girlfriend crashes their car into a wall trying to kill both of them. She dies, but he lives, horribly disfigured. The doctors are unable to help him and he fears his face has ruined any chance he has with Sofia. However, she isn't swayed by his appearance and lets him know she loves him too. At the same time, a revolutionary new plastic surgery procedure allows him to restore his original good looks, but it seems it is not without a price.